The Mobile Application Hacker's Handbook. (July 2015) - Unknown
Abstract : Even though malware on desktop systems shows no signs of abating, many people are shifting their attention to an arguably faster-growing menace – security on mobile devices. It's not just that security issues are increasing in number on platforms like Android – which they are, and rapidly at that – but that mobile devices represent a chink in any organisation's armour.